What drives organizations to switch to cloud ERP systems? The impacts of enablers and inhibitors. Issue 3 (2nd April 2020) - Chang, Yu-Wei
Abstract : Purpose: Switching to public cloud enterprise resource planning (ERP) systems not only provides financial and functional benefits to organizations, but also results in sunk costs of incumbent systems and uncertainty costs of cloud systems. The purpose of this study is to investigate the enablers and inhibitors concerning switching to cloud ERP systems at the organizational level. Design/methodology/approach: Data were collected from 212 top managers and owners of the enterprises in Taiwan, and 10 hypotheses were examined using structural equation modeling. Findings: Technological (system quality), organizational (financial advantage), and environmental contexts (industry pressure) are found to be the antecedents of switching benefits. Perceived risk of cloud ERP systems and satisfaction with and breadth of use of incumbent ERP systems are found to be the predictors of switching costs. Switching benefits positively affect switching intention, but switching costs negatively affect switching intention. Research limitations/implications: This study develops a theoretical model grounded in a set of theoretical foundations, including two-factor theory, technology-organization-environment (TOE) framework, information systems (IS) success model, and expectation confirmation theory (ECT). Two-factor theory is used to characterize switching benefits and costs that affect switching intention. Technological factors come from IS success model, and the factors affecting benefits are organized based on TOE framework. Sunk costs of incumbent ERP systems are developed based on ECT. Originality/value: Different from previous studies on cloud computing adoption, this study provides insights into switching intention to cloud computing. The study also proposes an integrated model grounded in multiple perspectives to explain organizations' decisions to switch to cloud ERP systems. These findings help cloud service providers better understand how to promote cloud ERP adoption from technical, organizational, and environmental perspectives.